Salvia mellifera—How Does It Alleviate Chronic Pain? - James David Adams; Steven Guhr; Enrique Villaseñor (Medicines, 2019)
Black sage, Salvia mellifera, can be made into a sun tea that is used as a foot soak to treat pain patients. The monoterpenoids and diterpenoids in the preparation penetrate the skin of the feet and stop the pain chemokine cycle, which may be the basis of chronic pain. Several chronic pain patients have reported long-term improvements in their pain after treatment with the preparation.